Cloning of human serum albumin (HSA) cDNA and construction of H. Brasiliensis laticifer-expression vector - Shixiang Bao; Hua Ling; Huiqin Huang; Jiasen Lv; Ming Cong (Proceedings of IRRDB Conference: NR Industry: Responding to Globalization, 7-8 September 2004, Kunming International Convention & Exhibition Center, China. pp.104-110.)
To clone mature Human Serum Albumin (HSA) cDNA, total RNA was isolated from fetal liver, and then HSA cDNA was clones by reverse transcriptase-polymerase chain reaction (RT-PCR). It was analyzed by sequencing and BLAST similarity searching. The HSA cDNA fragment clones was 1758 base pairs in length, and showed similarity of 99.6;compared with the reported sequence. At the same time, upstream sequence of rubber elongation factor (ref) of H. brasiliensis was clones by specific PCR. Cloned sequences were 306bps and 378bps. To identify its function, ref upstream sequence was used to promote transient expression of GUS gene in H. brasiliensis leaf. The results indicated that GUS could transiently express when promoted by ref upstream sequence could promote GUS expression in latex-expression system. We deduced that it could probably promote HSA cDNA to express in H. brasiliensis. So a laticifer-expression vector was constructed and it will be used to transfer HSA cDNA into H. brasiliensis. Finally a transgenic plant expressing HSA in laticifers will be obtained.
Keywords: Cloning; Human serum albumin